2004
DOI: 10.1530/rep.1.00076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of feline zona pellucida glycoprotein B-derived synthetic peptides on in vitro fertilization of cat oocytes

Abstract: Although immunocontraception based on porcine zona pellucida (ZP) proteins is widely applied in many species, it is not suitable for cat contraception due to the lack of cross-reactivity. Since the first ZP gene expressed during oocyte growth in domestic cats is ZPB, we assumed that immunization with feline ZPB (fZPB)-derived synthetic peptides may cause irreversible infertility, which would be preferable in stray cats. Thus, the present study evaluated the immunogenicity and the contraceptive potential of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…In the past 20 years, numerous studies have been performed in domestic cats investigating in vitro oocyte maturation, IVF (Johnston et al 1989, Goodrowe et al 1991, Jewgenow et al 1997, Ringleb et al 2004, influences of ovarian status and season on the oocyte maturation or embryonic developmental potency (Spindler & Wildt 1999, Freistedt et al 2001, as well as in vitro embryo culture conditions (Herrick et al 2007) and embryo cryopreservation (Gomez et al 2003). Although dramatic improvements have been made for in vitro techniques, artificially produced embryos still demonstrate lower developmental competence than in vivo embryos (Roth et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, numerous studies have been performed in domestic cats investigating in vitro oocyte maturation, IVF (Johnston et al 1989, Goodrowe et al 1991, Jewgenow et al 1997, Ringleb et al 2004, influences of ovarian status and season on the oocyte maturation or embryonic developmental potency (Spindler & Wildt 1999, Freistedt et al 2001, as well as in vitro embryo culture conditions (Herrick et al 2007) and embryo cryopreservation (Gomez et al 2003). Although dramatic improvements have been made for in vitro techniques, artificially produced embryos still demonstrate lower developmental competence than in vivo embryos (Roth et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…IHC studies demonstrated that pZP antibodies did not bind to cat oocytes, but fZP antibodies did. In a third study, antibodies raised in rats against a portion of the fZP protein containing an epitope recognized by rabbit anti-fZP serum (ZPB amino acid residue 130– 149) reduced in vitro sperm binding and fertilization of feline oocytes 37. These studies are contradictory, clouding the issue of whether ZP has contraceptive potential in cats.…”
Section: Discussionmentioning
confidence: 99%
“…All cumulus-oocyte complexes (COCs) were collected by gentle disruption of the antral follicles. Oocytes with complete compact cumulus and uniform, dark cytoplasm were cultured as described previously [37], with one variation in the method: about 20 companion COCs obtained from domestic cats ovariectomized the same day were added to each well in a Tissue Culture Insert (10 mm, NUNC) to keep them separated from the recovered eggs. After in vitro maturation for 24 h the oocytes were analysed under a phase contrast microscope for polar body extrusion and were stained with aceto-orcein to confirm nuclear maturation.…”
Section: Oocyte Collection and In Vitro Maturationmentioning
confidence: 99%